2015
DOI: 10.1063/1.4907353
|View full text |Cite
|
Sign up to set email alerts
|

Thermal characterization and analysis of microliter liquid volumes using the three-omega method

Abstract: Thermal phenomena in many biological systems offer an alternative detection opportunity for quantifying relevant sample properties. While there is substantial prior work on thermal characterization methods for fluids, the push in the biology and biomedical research communities towards analysis of reduced sample volumes drives a need to extend and scale these techniques to these volumes of interest, which can be below 100 pl. This work applies the 3ω technique to measure the temperature-dependent thermal conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Due to the temperature coefficient of resistance of the metal, the resistance of the line is also perturbed at frequency 2ω, leading to an overall voltage oscillation at frequency 3ω, which is detected using a lock-in amplifier. We implement this measurement by growing the NW array directly above an electrically-isolated metal line that is 49 and is adapted to contain a buried electrode to facilitate electrodeposition onto the center of the device 50 as shown in Fig. 4.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the temperature coefficient of resistance of the metal, the resistance of the line is also perturbed at frequency 2ω, leading to an overall voltage oscillation at frequency 3ω, which is detected using a lock-in amplifier. We implement this measurement by growing the NW array directly above an electrically-isolated metal line that is 49 and is adapted to contain a buried electrode to facilitate electrodeposition onto the center of the device 50 as shown in Fig. 4.…”
Section: Resultsmentioning
confidence: 99%
“…26is affected by κ and ρC can be examined by studying the sensitivity of the model to each material parameter. 36,42 The sensitivity of the model relates how much the measured temperature rise would change in response to a change in the sample thermal conductivity (κ) or heat capacity (ρC), via the normalized derivative with respect to thermal conductivity, (κ/T) ⋅ ∂T/∂κ, or heat capacity, (ρC/T) ⋅ ∂T/∂ρC. Figure 8 shows the in-phase and out-of-phase sensitivities of the hot-wire measurement (using a 5 mm long, 25 μm diameter Pt wire) to sample κ and ρC over a 1-1000 Hz spectrum for gas-like [ Fig.…”
Section: Model Sensitivitymentioning
confidence: 99%
“…The 3ω method has primarily been used for characterizing solid materials although earlier specific heat spectroscopy studies [37][38][39] have shown the promise of frequency-domain techniques for investigating the properties of liquids and phase changes. More recent work has been done to extend 3ω method to liquids [40][41][42] and soft materials; 43 however, they still retain the basic geometry of the planar 3ω method that includes parasitic heat flux through the supporting substrate that usually has much higher thermal conductivity than the liquid or soft material being studied. In order to ensure as much of the generated heat flux propagates through the liquid sample, wire geometries immersed or embedded in the sample are ideal, limiting the parasitic conduction pathways to the wire axis itself.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of in-situ thermal conductivity measurement of flowing fluids could be useful for the operational safety and diagnosis of these systems [6,7]. Despite a multitude of techniques available for the thermal conductivity measurement of stagnant fluids, including the transient hot-wire (THW) method [8,9], steady-state method [10][11][12], laser flash analysis (LFA) [13,14], 3ω technique [6,15,16], and time or frequency domain thermoreflectance techniques (TDTR/FDTR) [17], there are still challenges of applying these techniques for in-situ diagnostics, especially under the harsh environment (such as high temperature and/or with corrosive fluids).…”
Section: Introductionmentioning
confidence: 99%